(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Testo della Relazione tenuta al Dialogue Seminar sul tema "Freedom of Religion: A Fundamental Right in a Rapidly Changing World", organizzato da The Church and Society Commission of the Conference of European Churches (CEC), con The Commission of the Bishops’ Conferences of the European Community (COMECE), e con The Bureau of European Policy Advisors (BEPA), European Commission (Brussels, 30 marzo 2012), nel corso della Prima Sezione dedicata al tema "Freedom of Religion in the context established by the Treaty of Lisbon".